Comparison of Long-Term Survival Between cT1N0 Stage Esophageal Cancer Patients Receiving Endoscopic Dissection and Esophagectomy: A Meta-Analysis - Lu, Wei; Li, Peng; Wen, Wu; Jian, Yi (Frontiers in Surgery, 2022)
Background Endoscopic dissection (ED) shows relatively high clinical value in early esophageal cancer (cT1N0) such as lower incidence of postoperative complications and hospitalization costs and enhanced recovery. However, whether ED still has certain advantages over esophagectomy in terms of long-term survival remains unclear. Purpose The aim of this meta-analysis was to compare the long-term outcomes of ED and surgery in the treatment of cT1N0 esophageal cancer. Methods Several electronic databases including the PubMed, EMBASE, Web of Science and Cochrane Library databases were searched up to April 7, 2022 for studies which compared the overall survival (OS) and disease-specific survival (DSS) of cT1N0 esophageal cancer patients receiving the ED or esophagectomy. The hazard ratios (HRs) and 95% confidence intervals (CIs) were combined and all statistical analysis was conducted through STATA 15.0 software. Results A total of 12 studies involving 3,732 patients were enrolled. No significant difference in the OS between ED and surgery groups was observed (HR = 0.78, 95% CI, 0.59–1.04, p = 0.089). However, the DSS of the ED group was significantly longer than that of the surgery group (HR = 0.56, 95% CI, 0.39–0.82, p = 0.003). Conclusion In overall, the current evidence manifested that the long-term survival of cT1N0 esophageal cancer patients undergoing ED was not worse than that of patients undergoing esophagectomy. ED may be considered as the primary treatment for cT1N0 esophageal carcinoma patients.